Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I was reading my notes and I came across these 2 lines, Im wondering how did it go from $\sin$ to $\sinh$?

$-5\sin i\pi$

$ = -5i\sinh \pi$

share|cite|improve this question

$$\sin z=\frac{e^{iz}-e^{-iz}}{2i}$$

$$\sinh z=\frac{e^{z}-e^{-z}}{2}$$

In the first line, put $z=i\pi$ and note that $\dfrac{1}{i}=-i$.

share|cite|improve this answer

You can start with the basic definitions $\sinh(x) = (e^x-e^{-x})/2$ and $e^{ix} = \sin(x)+i\cos(x)$, from the second one you can derive $\sin(x) = (e^{ix}-e^{-ix})/2$. Substitute $i\pi$ for $x$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.